Reliabilitas Ujian Akhir Bahasa Inggris untuk Mahasiswa Manajemen - Astuti, Peni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2021)
This research aimed to determine the reliability of the final English test for the first semester of Management students of Faletehan University. The writer would like to know whether the final English test for the first semester of Management students was reliable. The writer's method in this research was a descriptive quantitative analysis method with Pearson’s Product Moment Correlation technique to describe the reliability. The hypotheses that would be tested were: (1) Final English test for the first semester of Management students was reliable. (2) English final test for the first semester of Management students was unreliable. The research instrument was the parallel test of the final English test for the first semester of Management students. The respondent used was 28 students. After analyzing, the writer got r o = 0.87 with the significant standard of 0.0500 and r t = 0.312. Since r o 0,87 > r t 0.312, so Hi was accepted and Ho was rejected and the conclusion of this research states that the final English test for the first semester of Management students had been reliable.